2015
DOI: 10.1103/physreva.92.052103
|View full text |Cite
|
Sign up to set email alerts
|

Parity-time symmetry in a flat-band system

Abstract: In this paper we introduce Parity-Time (PT ) symmetric perturbation to a one-dimensional Lieb lattice, which is otherwise P-symmetric and has a flat band. In the flat band there are a multitude of degenerate dark states, and the degeneracy N increases with the system size. We show that the degeneracy in the flat band is completely lifted due to the non-Hermitian perturbation in general, but it is partially maintained with the half-gain-half-loss perturbation and its "V" variant that we consider. With these per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…The latter approach was used in Ref. [7] where E A in one unit cell of the Lieb lattice is detuned by G/10, and the resulting defect state confirms an evanescent tail given by Eq. (6).…”
Section: Evanescent Waves In the Absence Of Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…The latter approach was used in Ref. [7] where E A in one unit cell of the Lieb lattice is detuned by G/10, and the resulting defect state confirms an evanescent tail given by Eq. (6).…”
Section: Evanescent Waves In the Absence Of Disordermentioning
confidence: 99%
“…Systems that exhibit flat bands have attracted considerable interest in the past decades, including optical [1,2] and photonic lattices [3][4][5][6][7], graphene [8,9], superconductors [10][11][12][13], fractional quantum Hall systems [14][15][16] and exciton-polariton condensates [17,18]. As the name suggests, a flat band is dispersionless, or in other words, its density of states (DOS) diverges at a particular energy, known as the flat band energy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of Kerr nonlinearity in the system may exhibit conical diffraction at the Dirac cone [30,34]. Due to their simple geometry, Lieb lattices are in the focus of research in ultracold systems as an optical trap for fermions [35], providing existence of magnon Hall effect in spite of the presence of inversion symmetry [18], protection and formation of robust zero modes localized at point defects [36], optimization of the BCS critical temperature and superfluid weight [37], and lifting the flat band modes by PT-symmetric perturbation due to thresholdless PT-symmetry breaking [38]. Moreover, it has been shown that the Lieb lattice acts as a good platform for analyzing various topological transitions in Chern insulators [20,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ramezani has shown that a flat band with completely real eigenvalues can exist in a quasi-1D PT photonic lattice 36 . This PT symmetric flat band was realized by fine-tuning gain/loss levels, and it is not obvious what features of this model, compared to earlier models [33][34][35] , make it possible. Here, we show that PT symmetric flat bands generically occur in non-Hermitian lattices with a bipartite sublattice symmetry hosting a differing number of sites per sublattice 37,38 .…”
Section: Introductionmentioning
confidence: 97%
“…An important question is whether the existence of flat bands is compatible with non-Hermiticity, and if so whether the presence of EPs might alter the behavior of the flat band states. Previous studies have analyzed how Hermitian flat bands are changed by the application of non-Hermitian perturbations [33][34][35] , finding either that the symmetries protecting the flat band states are spoilt, or that the flat bands simply acquire nonzero gain or loss (breaking PT symmetry). Recently, Ramezani has shown that a flat band with completely real eigenvalues can exist in a quasi-1D PT photonic lattice 36 .…”
Section: Introductionmentioning
confidence: 99%